What Makes Gen Z in Indonesia Use P2P Lending Applications: An Extension of Technology Acceptance Model - Yanto; Agung Putra; Zikri Rahmani; M. Afdal Samsudin (Faculty of Computer Science Universitas Indonesia, 2024)
This study aims to determine the factors influencing Gen Z members in Indonesia using P2P lending applications. This study extended TAM by collaborating with important constructs, such as trust, perceived risk, and hedonic motivation, to explain Generation Z’s intention to use P2P lending applications. This study utilized an online survey to acquire data. The total sample size was 305 users of P2P lending applications from Generation Z. The obtained data were then analyzed using PLS-SEM. The results show that perceived usefulness has no effect on the intention to use P2P lending applications. Meanwhile, trust mediates the relationship between perceived ease of use and perceived usefulness on intention to use P2P lending applications. The results show that Generation Z's intention to use P2P lending applications is influenced by technological sophistication factors, the belief that P2P lending applications guarantee their privacy concerns and security risks, and the existence of pleasant experiences.